Consistent assignment of the vibrations of symmetric and asymmetric meta-disubstituted benzenes - Kemp, David J.; Tuttle, William D.; Jones, Florence M.S.; Gardner, Adrian M.; Andrejeva, Anna; Wakefield, Jonathan C.A.; Wright, Timothy G. (Elsevier, 2018)
The assignment of vibrational structure in spectra gives valuable insights into geometric and electronic structure changes upon electronic excitation or ionization; particularly when such information is available for families of molecules. We give a description of the phenyl-ring-localized vibrational modes of the ground (S0) electronic states of sets of meta-disubstituted benzene molecules including both symmetrically- and asymmetrically substituted cases. As in our earlier work on monosubstituted benzenes [A. M. Gardner and T. G. Wright. J. Chem. Phys. 135 (2011) 114305], para-disubstituted benzenes [A. Andrejeva, A. M. Gardner, W. D. Tuttle, and T. G. Wright, J. Molec. Spectrosc. 321 (2016) 28], and ortho-disubstituted benzenes [W. D. Tuttle, A. M. Gardner, A. Andrejeva, D. J. Kemp, J. C. A.Wakefield and T. G. Wright, J. Molec. Spectrosc. 344 (2018) 46], we conclude that the use of the commonly-used Wilson or Varsányi mode labels, which are based on the vibrational motions of benzene itself, is misleading and ambiguous. Instead, we label the phenyl-ring-localized modes consistently based upon the Mulliken (Herzberg) method for the modes of meta- difluorobenzene (mDFB) under Cs symmetry, since we wish the labelling scheme to cover both symmetrically- and asymmetrically-substituted molecules. By studying the vibrational wavenumbers obtained from the same force-field while varying the mass of the substituent, we are able to follow the evolving modes across a wide range of molecules and hence provide consistent assignments. We assign the vibrations of the following sets of molecules: the symmetric metadihalobenzenes, meta-xylene and resorcinol (meta-dihydroxybenzene); and the asymmetric meta-dihalobenzenes, meta-halotoluenes, meta-halophenols and meta-cresol. In the symmetrically-substituted species, we find two pairs of in-phase and out-of-phase carbon substituent stretches, and this motion persists in asymmetrically-substituted molecules for heavier substituents; however, when at least one of the substituents is light, then we find that these evolve into localized carbon-substituent stretches.